Theories of delinquency: an examination of explanations of delinquent behavior - Shoemaker, Donald J. (Oxford University Press, 2018)
"Theories of Delinquency is a comprehensive survey of the theoretical approaches towards understanding delinquent behavior. Donald J. Shoemaker aptly presents all major individualistic and sociological theories in a standard format with basic assumptions, important concepts, and critical evaluations. Theories covered include biological and psychological explanations, anomie and social disorganization, differential association, drift theory, labeling theory, critical theories, and explanations of female delinquency. Now in its seventh edition, Theories of Delinquency contains up-to-date discussions based on current research of new developments in the area of social disorganization theory and analysis of related concepts such as collective efficacy and place criminology. This edition also offers a fresh look at bio-social and psychological connections to crime and delinquency, and reconsiders the importance of theoretical concepts in the final chapter. Clearly written, consistently organized, and now thoroughly updated, Theories of Delinquency remains essential reading for advanced undergraduate and graduate students of crime and delinquency"--